Education of students in higher educational medical universities of Ukraine taking into account competence-oriented educational technologies - Liliya Batyuk; Oksana Zhernovnykova (Kazimierz Wielki University, 2016)
A higher educational institution is called upon to contribute to a constant increase in the degree of development and readiness of students for self-educational activities on a proactive basis. The features of training and formation of competences among medical students in the general theoretical aspect are considered as a fundamental condition for the successful implementation of future professional activities, which provides the ability to quickly and correctly use knowledge, experience, and personal qualities, ensures their control and restructuring of activities when obstacles appear. The development of the proposed theoretical and practical material in medical universities is of a general nature, including and substantiating the goal, objectives and structure of the formation of the personality of a future professional. The application of the competence-based approach and the practical orientation of training in higher educational medical institutions of Ukraine are designed to form student's not only preliminary, but also situational readiness. In the context of considering competence-oriented educational technologies in higher educational universities of Ukraine, including pedagogical and educational technologies, is the readiness of future specialists for productive independent and responsible action in professional activities and everyday life. The teachers of medical universities are obliged to ensure the achievement of this result using a complex integral image of the final result of education at the university in the direction of training (specialty), which is based on the concept of "competence".